2018
DOI: 10.1039/c7ta09260a
|View full text |Cite
|
Sign up to set email alerts
|

Biotemplating: a sustainable synthetic methodology for Na-ion battery materials

Abstract: Dextran biotemplating offers a novel, sustainable and fast reduced-temperature synthetic route for energy storage materials (e.g. P3-Na2/3Ni1/3Mn2/3O2) with fine control over particle size and morphology that offers a new route to optimizing electrochemical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…If water intercalation did any lasting damage, to the extent that electrochemical performance would be affected, it would likely be evident even after drying under vacuum at 120 °C. As shown in our previous study, the biotemplating synthetic process produces agglomerated particles of P3-NNM with individual average particle sizes in the range of 100-200 nm (Zilinskaite et al, 2018), which can be observed in Figures 3A,B. Such morphologies have been found in other dextran-templated materials (Walsh et al, 2003).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…If water intercalation did any lasting damage, to the extent that electrochemical performance would be affected, it would likely be evident even after drying under vacuum at 120 °C. As shown in our previous study, the biotemplating synthetic process produces agglomerated particles of P3-NNM with individual average particle sizes in the range of 100-200 nm (Zilinskaite et al, 2018), which can be observed in Figures 3A,B. Such morphologies have been found in other dextran-templated materials (Walsh et al, 2003).…”
Section: Resultssupporting
confidence: 77%
“…P3-NNM was synthesized by dextran biotemplating, as reported previously (Zilinskaite et al, 2018). The reagents were obtained from Sigma-Aldrich (UK) with 98+% purity and used without further treatment.…”
Section: Materials and Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…This matrix subsequently 'traps' metal cations from solution and allows the formation of a homogeneous aqueous gel, which acts as a precursor for sol-gel synthesis (see the biopolymer review 55 ). The process promotes nano-sized particle formation at reduced temperatures compared to that of traditional solid state methods, with the biotemplate removed by the thermal treatment 56 .…”
Section: Ideal Garnets Have a General Formulamentioning
confidence: 99%
“…Dextran has also been used with this purpose. Using this template allowed the authors to control the morphology of the nanoparticle, which exhibited a higher energy storage capacity than traditionally created materials after the same conditions (103.1 mAh g −1 compared to 80.1 mAh g −1 after 10 cycles, respectively) [133].…”
Section: Energy Capture and Storagementioning
confidence: 99%